The form of upper Dental arch for Mosuli Adults (Acomputerized study) - Ne'am F Al-Obaidi; Khidhair A Al- Jumaili () (University of Mosul, College of Dentistry, 2011)
Aims: To find out the most frequent dental arch form in Mosuli adults. Establishment of the normative values of the upper dental arch dimensions. Materials and Methods: The sample of this study involved students from Mosul University, 95 students (58 females, 37 males) were selected. The age of the sample ranged between 18-25 years old. They were normal healthy individuals of Mosul origin. Full complement of permanent dentition, bilateral Class I molar and canine occlusion. The data recorded in this research were subjected to computerized statistical analysis using SPSS programs, including descriptive statistics (mean, standard deviation, minimum, maximum), Student's t-test was applied to test the significant differences between the genders. Results: There were highly significant differences between males and females of the vertical measurements, that males had larger arch length than females. Also, males had larger arch width with a highly significant difference at p < 0.01 in all width dimensions in maxillary arches. It could be noticed that the most prevalent arch form among the sample was the Mid form followed by the Narrow and Wide then flat & pointed forms. Conclusions: The mid arch form is the most frequent arch form followed by other types. All the measured dimensions (width and length) have significantly greater mean value in males than in females with significant difference for linear measurements. no significant difference in ratio between genders.